2010
DOI: 10.1152/ajprenal.00503.2009
|View full text |Cite
|
Sign up to set email alerts
|

Angiotensin type 2 receptor actions contribute to angiotensin type 1 receptor blocker effects on kidney fibrosis

Abstract: Angiotensin type 1 (AT1) receptor blocker (ARB) ameliorates progression of chronic kidney disease. Whether this protection is due solely to blockade of AT1, or whether diversion of angiotensin II from the AT1 to the available AT2 receptor, thus potentially enhancing AT2 receptor effects, is not known. We therefore investigated the role of AT2 receptor in ARB-induced treatment effects in chronic kidney disease. Adult rats underwent 5/6 nephrectomy. Glomerulosclerosis was assessed by renal biopsy 8 wk later, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
54
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 73 publications
(58 citation statements)
references
References 52 publications
4
54
0
Order By: Relevance
“…Infusion of PD123 319 in a rat model of glomerulosclerosis induced by 5/6 nephrectomy significantly increased glomerular cell proliferation and kidney fibrosis compared with animals that were nephrectomized alone. 30 Increased collagen I levels have also been shown previously to upregulate MMP-14 expression at the mRNA level, 31 which supports our findings. Moreover, fibrotic tissue remodeling after injury is associated with vascular damage and leakage, which has been shown to be associated with type I collagen remodeling and increased MMP-14 activity in mouse models of age-related dermal fibrosis.…”
Section: Discussionsupporting
confidence: 91%
“…Infusion of PD123 319 in a rat model of glomerulosclerosis induced by 5/6 nephrectomy significantly increased glomerular cell proliferation and kidney fibrosis compared with animals that were nephrectomized alone. 30 Increased collagen I levels have also been shown previously to upregulate MMP-14 expression at the mRNA level, 31 which supports our findings. Moreover, fibrotic tissue remodeling after injury is associated with vascular damage and leakage, which has been shown to be associated with type I collagen remodeling and increased MMP-14 activity in mouse models of age-related dermal fibrosis.…”
Section: Discussionsupporting
confidence: 91%
“…Consistent with these observations, both mRNA and protein levels of type IV collagen and fibronectin were significantly increased in PcKOTsc1 glomeruli ( Figure 2, C and D). Moreover, we also observed that mRNA and protein levels of TGF-β1 were significantly enhanced ( Supplemental Figure 2, G and H), whereas the protein expression but not amount of mRNA for angiotensin type 2 receptor (AT2R), which may have renoprotective functions, was reduced in PcKOTsc1 mouse glomeruli (Supplemental Figure 2, G and I) (25)(26)(27). mTORC1 activation in podocytes causes podocyte injury and proteinuria.…”
Section: Activation Of Mtorc1 In Podocytes In Dn Systemic Administramentioning
confidence: 85%
“…Within the glomerulus, Ang II decreases the ultrafiltration coefficient and modulates glomerular capillary permselectivity, leading to proteinuria. It has been reported that Ang II directly influences the functions of podocytes dependent on the Ang II type 1 receptor (44,45). A large body of evidence supports that inhibition of the renin-angiotensin system mitigates many deleterious processes in podocytes, thereby reducing the extent of injury.…”
Section: Discussionmentioning
confidence: 99%